EFEKTIVITAS PENGGUNAAN E-KTP DALAM PEMUNGUTAN SUARA PADA PEMILIHAN UMUM TAHUN 2019 DI KOTA PEKANBARU - Adek Sutriyah; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The creation of an effective and efficient general election is the purpose of organizing the elections. However, problems related to elections are still occurring today. Starting from the issue of selector list, voice mail to vote. Where the voting process relates to the use of E-KTP. Pekanbaru was one of the most popular elections in the year 2019. The Pekanbaru City General Election Commission as the organizing Committee was examined using the theory of Duncan (in Steers, 1985:53) quoted by Kharisma (2017:5). Methods of study used qualitative methods with a descriptive approach and technique of determination of informant using purposive technique. The results showed that the use of E-Ktp in voting in the elections in 2019 has notbeen effective there are factors that inhibit the implementation of such as: community participation, communication, data used, human resources, and facilities and infrastructure.          Keywords: effectiveness, E-KTP, general election